Artificial Intelligence in Climate Finance: Enhancing Green Investment, Carbon Risk Assessment and Capital Allocation (Journal of Asian Development Studies, 2025)
Artificial intelligence (AI) has increasingly become a transformative tool in climate finance,enabling firms to enhance green investment strategies, assess carbon risk more accurately, andoptimize capital allocation. This study investigated the role of AI in promoting sustainable financeby examining its impact on investment decisions, risk mitigation, and ESG evaluation. Data werecollected from multiple firms employing AI-based analytics to support green financial initiatives,and analysed using descriptive statistics, frequency distributions, and comparative evaluation ofAI adoption levels, green investment allocation, and carbon risk assessment accuracy. Thefindings indicated that firms with higher AI integration achieved more precise risk assessments,allocated capital more efficiently to sustainable projects, and demonstrated improved resilienceto climate-related financial uncertainties. Despite these benefits, challenges were identified,including limitations in data quality, algorithmic bias, disparities in institutional readiness, andenvironmental impacts associated with energy-intensive AI computations. The study alsohighlighted that effective AI adoption required robust data governance, standardized ESGreporting frameworks, and employee training to maximize decision-making efficiency.Recommendations emphasized ethical implementation, regulatory guidance, and the integrationof AI technologies with sustainability objectives to ensure both financial and environmental gains.Future research should explore cross-sectoral adoption, longitudinal impacts, and advanced AImethods such as reinforcement learning and blockchain-enabled analytics. Overall, the studydemonstrated that AI not only strengthens analytical capabilities but also fosters strategicalignment between financial performance and environmental sustainability.